Çorum Kent Merkezindeki Yeşil Alanların Nicelik Ve Nitelik Açısından Değerlendirilmesi - Özdindar, Alev (Fen Bilimleri Enstitüsü, 2015)
Kentsel yeşil alanlar, kente çok yönlü değer katan, kentsel mekan kalitesi ve insan yaşamını doğrudan etkileyen kentin en önemli parçasıdır. Kentsel yeşil alanlar, tesis edildiği andan itibaren değişen ve gelişen, bu değişim ve gelişime paralel olarak da ekolojik, rekreasyonel ve estetik etkileri ile kentin yapısını olumlu yönde etkileyen dinamik sistemlerdir. Giderek artan kent nüfusu, hızlı yapılaşmayı da beraberinde getirmekte ve bu durumun bir sonucu olarakta kentsel yeşil alanların yapı bloklarına dönüştüğü görülmektedir. Sonuca ters orantılı olarak kentsel yaşamın insanlar üzerindeki  baskısı  insanların yeşil alanlara olan ihityacını artırmaktadır. Mevcut imar mevzuatında kentlerde bir yeşil alan sistemi oluşturulmasına ilişkin yaptırım bulunmaması, yeşil alan sistemlerinin bütüncül olmayan ve kısa vadede kentsel büyümeyi öngören  planlama yaklaşımları ile oluşturulması kentte  ki yeşil alan yetersizliğinin temel nedenleri arasındadır. Kentlerde yeşil alan sistemleri kentlerin coğrafi konumu, arazai yapısı, iklimi, demografik ve sosyo kültürel yapısı gibi özelliklerine göre nitelik ve nicelik bakımından farklılık gösterir. Çorum gibi küçük ölçekli, hızla yapılaşmakta olan, ekonomisi ağırlıkla sanayiye dayalı, denize kıyısı bulunmayan ve sosyal yapısı içe dönük  kentlerde insanların yeşil alan gereksinimleri oldukça fazladır. Bu nedenle insanlar evlerinden minimum yürüyüş mesafesinde ulaşabilecekleri yeşil alanlara ihtiyaç duymaktadır. Bu durum kent içinde ki hızlı yapılaşmayla birlikte  planlama girdisi olarak değerlendirildiğinde bütüncül yeşil alan sistemlerinin oluşturulasına engel teşkil etmekte, kent içindeki yeşil alanların niteliğini olumsuz yönde etkilemektedir. Tezin çalışma alanı, Çorum kent merkezinde 14 mahallede konumlanan yeşil alanları kapsamaktadır. Çalışma sürecinde öncelikle;  yerinde analiz bulguları, belediye envanterleri ve  Coğrafi Bilgi Sistemi yazılımlarından biri olan  CitySurf programından elde edilen çeşitli yıllara ait hava fotoğrafları çakıştırılıp  işlenerek grafiksel veriler elde edilmiştir. Edinilen veriler doğrultusunda belirli  dönemlerde  kentte konumlanan yeşil alanlar belirlenmiş ve bu alanların   tarihsel süreç içindeki değişimi ortaya koyulmuştur. Çalışmanın devamında kent merkezinde bulunan yeşil alanların mahallelere göre dağılımı incelenmiş, mahalle ölçeğinde kişi başına düşen yeşil alan miktarları ortaya koyulmuştur. Son bölümde kentte konumlanan yeşil alanlar İsveç standartlarına göre değerlendirilmiş, standardı sağlayan 32 adet konut öbeği parkı nicelik ve nitelikleri bakımından incelenmiştir. Mevcut durumun analiz edilmesi üzerine kentte konumlanan yeşil alanların nicelik ve   nitelik bakımından yetersiz olduğu saptanmış, kent merkezinin genelinde mevcut durumun iyileştirilmesi adına öneriler sunulmuştur.

Urban green spaces, urban versatile value -added , the most important part of the city affecting the quality of urban spaces and human life directly. Urban green spaces, changing from the moment it is established and developed , in parallel with the development of this change and the ecological , recreational and aesthetic effects on the structure of the city are dynamic systems that influence positively. A growing urban population , and to bring about rapid construction is seen that in this case the return to the building blocks of urban green areas as a result. The pressure on people in urban life is inversely proportional to the results to improve the people looking to upgrade green areas. In this context, the formation of healthy green spaces and high-quality urban environment is of great importance . In particular, the life of today's urban green areas; citizen of the mental and physical requirements to meet than the protection of natural resources, residential areas for the development of trade and industry of tourism in the creation of buffers , the development of urban aesthetic , until it reaches the regulation of pedestrian and vehicle circulation has assumed many functions . These functions outlined in urban life physical, psychological , ecological, climatic, economic and aesthetic emerges as functions. Green spaces contribute to the improvement of urban climate to create their own microclimate . Structures and hard floors more solar energy than the amount of green space in urban areas. Plants make the shade by leaves and prevents sunlight from reaching the ground directly . In addition, the green areas in the regulation of air humidity, dust and gas air pollutants in keeping the balance of the wind direction and intensity, and has active role in the prevention of erosion caused by runoff. Green areas at the same time eliminating the monotony of mass formed by the structure contribute to the urban aesthetic . From one hand, a result which contributes to the aesthetic sense of the physical structure; creating a network of green on the other hand they form a base for construction in the future. A green space system in the absence of sanctions for the establishment in the city in the current zoning regulations, non-integrated green space system and the creation of the planning approach envisages the urban growth in the short term are the main causes of green space deficiency in the city. The geographic location of city green space system in the city, land structure, climate, demographic and socio-cultural structures vary in quality and quantity as compared to the properties. The size and density of the area where the settled population, age distribution should be taken into account in determining the need for green space. Common problems occur in this matter; response to increasing population, decreasing the norm is the application of the system. The city's character, structure condition of the subject and the city is another important factor that determines the need for green spaces where citizens heard. Garden house with a density of metropolis cities that vary the intensity of green space needs of people living in high-rise buildings. Çorum such as small-scale , rapidly being structured , predominantly industrial economy based on the sea coast and social structure without green space requirements are a lot of people in town introverted . Therefore, people are in need of green space accessible to a minimum walking distance from their homes. This case considered when planning went along with the rapid construction in the city to create a barrier of integrated green space system affect negatively the quality of green space in the city . The working area of the thesis, Çorum covers green areas in the city center which is located in 14 neighborhoods. Akkent, Bahçelievler, Bukhara, Çepni, Çöplü, Gülabibey, Kale , Karakeçili, Kunduzhan, Mimar Sinan, Ulukavak, Üçtutlar, Yavruturna and Yeniyol Neighborhoods . First, the Worker Process; site analysis findings, municipal inventory, GIS aerial photographs of various years with CitySurf obtained from one of the software programs has been obtained by processing graphical data. The data obtained in accordance with the city's construction the rate of expansion of the border, which is located in the city green areas identified in historical perspective change of this area has been put forward. In the study, development of green areas in the city have been examined in five separate periods, the examination has been put forward from 1923 to 2015 years of urban change. As of 1990, only green fields just as the people considered active Uses the city were also addressed, as are value-add to the aesthetic elements. The 2000s continued to increase to the point improvement compared to previous years, the year 2000 to 2015 was built 140 units, including 16-year period in the park. The size varies between 147 m² and 71.143 m². The obtained data were analyzed in urban construction and population growth rate, the amount of green space per capita is higher than the rate of formation of new green areas remained in descending value, depending on the year. Considering the scale located in neighborhood green spaces in the city is seen that most of the parking spaces in the neighborhood of Ulukavak is at least Yavruturna parking space in the neighborhood. Given the amount of green space per capita green space in the neighborhood distribution Karakeçili maximum , while the minimum value is Yavruturna neighborhood . In total up to this day in the city it was determined to be 802. 398 square meters of green space assets . The city's population is 275. 610 people . In this context , it drops 2.9 square meters of green space per person in the entire city . Last chapter evaluated according to the Swedish standard green areas located in the city, the housing 32 provides the standard phrases were examined in terms of quantity and quality of the parks . Analyzing the current situation determined that the green space located on the city is inadequate in terms of quantity and quality, suggestions on the improvement of the current situation across the city center were presented.  There are detailed list  of green areas and parking areas in the city, written sources and theses list is about Çorum and 2015 development plan in addition of the thesis.
Evaluation Of Çorum City In Terms Of Quality And Quantity Of Green Space In The City Center
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Kentsel yeşil alanlar Kent parkları Çorum kent merkezi; Urban green areas Urban parks Çorum city center